5y-11=7(y+1)

Simple and best practice solution for 5y-11=7(y+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-11=7(y+1) equation:


Simplifying
5y + -11 = 7(y + 1)

Reorder the terms:
-11 + 5y = 7(y + 1)

Reorder the terms:
-11 + 5y = 7(1 + y)
-11 + 5y = (1 * 7 + y * 7)
-11 + 5y = (7 + 7y)

Solving
-11 + 5y = 7 + 7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7y' to each side of the equation.
-11 + 5y + -7y = 7 + 7y + -7y

Combine like terms: 5y + -7y = -2y
-11 + -2y = 7 + 7y + -7y

Combine like terms: 7y + -7y = 0
-11 + -2y = 7 + 0
-11 + -2y = 7

Add '11' to each side of the equation.
-11 + 11 + -2y = 7 + 11

Combine like terms: -11 + 11 = 0
0 + -2y = 7 + 11
-2y = 7 + 11

Combine like terms: 7 + 11 = 18
-2y = 18

Divide each side by '-2'.
y = -9

Simplifying
y = -9

See similar equations:

| (4u-6)(4+u)=0 | | -28=-4/9u | | 3n-n=12 | | 4w(w+2)(w-9)=0 | | (2/5)*j=15 | | (4x+43)/2=32 | | 2/5j=15 | | y^2-8y+16=36 | | 5(x-3)+64=-2x | | 3(6-x)=-5x-7-3x | | (2v+5)(7+v)=0 | | c=a+2b | | -8(c+6)=4(x-6) | | 5x-15.4=15.4(x-3.6) | | 18x^2-27x=-10 | | (6/y)(3y/6) | | 125=0.5x*(10+15) | | -6+18=7-1(4x+9) | | w^2+w-2=0 | | 8(c-4)=-2(c+6) | | -a^2-10a+25=25 | | 4.5(x-4)=-0.5x+22 | | 6(3a+14)=90 | | 0=x^2-32x-5 | | B^2+5b+1= | | 1/2t+3=5 | | (5x/4)+(x+4) | | 10=0.5*2*(6+x) | | 6x+3=9(x-4) | | 8x^2y+12xy^2= | | 6x+3=9x | | 1m-5=3m |

Equations solver categories